THE UTILIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGY TO SUPPORT FARMING SYSTEM IN PURWOREJO REGENCY - Septi Nurhasanah; Subejo Subejo; Dyah Woro Untari; Sri Peni Wastutiningsih (Universitas Sebelas Maret, 2026)
Technological development has encouraged the use of information and communication technology (ICT) in agriculture to support smarter, more efficient, and sustainable farming systems. This study is novel in examining ICT utilization across three contrasting topographies within a single regency, and in finding that farming experience reduces — rather than increases — ICT use, while land area outweighs access-based factors such as device ownership. Purworejo Regency is a relevant area for such analysis due to its varied land characteristics. This study aimed to identify the factors influencing ICT utilization among smallholder farmers who are members of farmer groups in Purworejo Regency. A quantitative descriptive approach was employed through a survey of 87 farmers in three subdistricts representing topographical variation, namely Bener, Ngombol, and Purwodadi. The data were analyzed using multiple linear regression. The results showed that farming experience had a negative and significant effect, while land area had a positive and significant effect on ICT utilization. Meanwhile, age, education, status in farmer groups, land status, and number of ICT devices owned had no significant effect. The novelty of this study lies in its focus on smallholder farmers in a geographically diverse agricultural area and in examining the local level determinants of ICT use. These findings provide useful insights for developing more targeted agricultural digitalization policies and extension programs.